Keterampilan Berbahasa Presenter Penyaji Berita pada Lembaga Penyiaran Televisi - Erka, Wirnita (Jurnal Ipteks Terapan, 2014)
Language skills consists of four aspects: listening skills, speaking skills, reading skills, and writing skills. exchanging skills are skills that have become smaller since language acquisition. In order, starting from listening, then speaking, reading and writing. Meet all four language skills for presenters, easily implement programs. Presenter is a person who appeared in front of the camera and read the news from the studio or the person who brought all kinds of television programs from the studio. Is the leading presenter of a television broadcaster, with the task of realizing the programs that have been designed previously. In the television broadcaster, presenter is in charge of energy in the studio, while on duty outside the studio is a journalist and reporter. Presenter divided into two, namely   newsreader and newsanchor. Having all four language skills are  essential for newsanchor, because the job requires; listening skills, speaking skills, reading skills and writing skills. Listening skills, newsanchor needed when doing the questions to the speakers. The answers were listened to presenters will continue to be developed through speaking skills to explore the root causes, so we get the solution of the problem according topics covered. Reading skills, needed newsanchor, when reading the audio-visual display related topics and writing skills required, at the time of preparation of the event, both reference  and pointer events and resource-related questions. Writing skills, newsanchor needed in preparation of the event. The management of television broadcasters, can quickly understand the idea or newsanchor chill place to work. Language skills greatly contribute to the smooth and successful presenter job newsanchor on television broadcasters.Keywords: Language skills, newsreader,  newsanchor, and  broadcaster